Deubiquitylating enzymes and their emerging role in plant biology - Isono, Erika; Nagel, Marie-Kristin (Frontiers in Plant Science, 2014)
Ubiquitylation is a reversible post-translational modification that is involved in various cellular pathways and that thereby regulates various aspects of plant biology. For a long time, functional studies of ubiquitylation have focused on the function of ubiquitylating enzymes, especially the E3 ligases, rather than deubiquitylating enzymes (DUBs) or ubiquitin isopeptidases, enzymes that hydrolyze ubiquitin chains. One reason may be the smaller number of DUBs in comparison to E3 ligases, implying the broader substrate specificities of DUBs and the difficulties to identify the direct targets. However, recent studies have revealed that DUBs also actively participate in controlling cellular events and thus play pivotal roles in plant development and growth. DUBs are also essential for processing ubiquitin precursors and are important for recycling ubiquitin molecules from target proteins prior to their degradation and thereby maintaining the free ubiquitin pool in the cell. Here, we will discuss the five different DUB families (USP/UBP, UCH, JAMM, OTU, and MJD) and their known biochemical and physiological roles in plants.